The effect of FRCA and WPSA on the strength properties of foamed concrete / Siti Shahidah Sharipudin, Ahmad Ruslan Mohd Ridzuan and Hamidah Mohd Saman - Sharipudin, Siti Shahidah; Mohd Ridzuan, Ahmad Ruslan; Mohd Saman, Hamidah (Universiti Teknologi MARA Cawangan Perlis, 2011)
In view of the escalating environmental problems faced in this millennium with consideration to the rapid depletion of natural resources, the use of by-products or waste materials from different industries are highly desirable. One such alternative is waste paper sludge ash (WPSA), a local by-product produced abundantly by the paper newsprint industry. It has been observed through previous studies that WPSA possesses pozzolanic characteristics in enhancing concrete properties. On the other hand, progressive development in the construction sector recently has contributed as the main producer of construction wastes, particularly concrete wastes. Therefore, the present paper investigates the strength development of lightweight foamed concrete produced with various replacements level of WPSA and ultrafine recycled concrete aggregate (FRCA) to the cement and sand content respectively. The cube specimens were casted in size 100 mm x 100 mm x 100 mm and water cured. The compressive strengths were evaluated at 3, 7, 28 and 60 days. The results of this study showed that the inclusion of WPSA and FRCA have significant influence on the development of strength properties of foamed concrete.